Charyzmaty w świadectwach epoki ojców apostolskich - Gajewski, Wojciech (Przegla̜d religioznawczy, 2021)
Many very interesting documents originate from the end of the first and beginning of the second century. Among them Didache, Ignatiana, Prima Clementis and the Letter of Barnaba deserve special attention. This article presents analysis of writings, concentrating on occurances of charismata and their intensity. The result of this research confirms their presence in different social environments: in Syro-Palestine ecclesias, Anatolia as well as in Italy. The aforementioned documents not only use the lexeme charima/ta, but also indicate significant role of the itinerant charismatics in that time. For this reason the author of Didache recommends, among others, close cooperation of local community with the itinerant charismatics. Also the charismatic triad: apostles - prophets - teachers is often mentioned. High concentration of the "spiritual gifts of grace" can also be found in The Shepherd by Hermas. Apart from visions, both in consciousness and in sleep, which the author experiences, he writes about prophets. Both of the mentioned writings contain warnings against false prophets, what by itself confirms the wide presence of this gift in Christianity from the turn of 1st and 2nd century. Other authors in their writings also confirm occurences of charismata.